PENGARUH LOVE OF MONEY, GENDER, DAN MORAL REASONING TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI DENGAN AKHLAKUL KARIMAH SEBAGAI VARIABEL MODERASI - Sa'diyah, Lummatus; Darmayanti , Novi; Kusmayasari, Dewi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the influence of Love of Money, Gender, and Moral Reasoning on the ethical behavior of accounting students, with Akhlakul Karimah as a moderating variable. The research method used a quantitative approach, with a survey of 175 accounting students from the 2021 intake from four universities in Lamongan Regency. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using the SmartPLS application. The results showed that Love of Money and Moral Reasoning significantly influenced student ethical behavior, while Gender did not. Akhlakul Karimah was shown to negatively moderate the relationship between Moral Reasoning and ethical behavior, but did not moderate the effects of Love of Money or Gender. The implications of this study demonstrate the importance of integrating religious values in accounting education to strengthen students' ethical character. The novelty of this study lies in the use of Akhlakul Karimah as a moderating variable in the context of accounting ethics in Indonesia.